1981
DOI: 10.1111/j.1365-2621.1981.tb04904.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the Breadfruit

Abstract: Nutrient content in the skin, stem plus heart and the pulp of very immature, immature, mature, and very mature breadfruits (Artocarpus communis J.R. & G. Forst.) was studied. In most cases they were found to vary widely depending on the part and the maturity of the fruit. The major component and the principal carbohydrate in alJ three sections and at alJ stages of maturity was starch (more than 50% of the total carbohydrates). Relatively good levels of the minerals Ca, K, and Fe and the vitamins niacin and rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
3
2

Year Published

1988
1988
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 2 publications
2
44
3
2
Order By: Relevance
“…The result showed that the breadfruit contained 89% of starch in dry basis. This result was higher compared to the findings of earlier studies, which were 69%; 67.9%; and 58% (Graham and de Bravo 1981;Loos et al 1981;Steve et al 1995). The presence of starch implied that the material could be converted into bio-ethanol.…”
Section: Characterization Of Breadfruit Starchcontrasting
confidence: 57%
“…The result showed that the breadfruit contained 89% of starch in dry basis. This result was higher compared to the findings of earlier studies, which were 69%; 67.9%; and 58% (Graham and de Bravo 1981;Loos et al 1981;Steve et al 1995). The presence of starch implied that the material could be converted into bio-ethanol.…”
Section: Characterization Of Breadfruit Starchcontrasting
confidence: 57%
“…Nutrient composition of cassava and breadfruit flours used in the diets is similar value to that reported earlier by Gohl (1981), Graham and de Bravo (1981), Udo (1981), Aregheore (1988), Ravindran and Sivakanesan (1995) and Susumu (1999). The composition of the forage is similar to values reported by Solomona (1988) and Aregheore (1999).…”
Section: Resultssupporting
confidence: 73%
“…The fruit can be processed into livestock feed. It has eighty percent starch (Graham and de Bravo, 1981) and the available carbohydrate content is similar to that of maize (Ravindran and Sivakanesan, 1995). On the other hand, cassava is typically a high energy, low protein, mineral-vitamin feed (Agudu and Thomas, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Breadfruit has been processed into many forms for utilization in the food industry. It has also been processed into starches [2] and into flour [3]. Studies on the modification of breadfruit starch involving heat-moisture-treatment and annealing, which entail modification of temperature and moisture content have been carried out and reported by Adebowale et al, [4].…”
Section: Introductionmentioning
confidence: 99%